Liability for Groundwater Contamination from Pesticides in the Godavari Plain of Parbhani district - Motekar *, S.C. (Recent Research in Science and Technology, 2011)
Some ground water samples in Parbhani district have had a designated Maximum Contaminant Limit (MCL) of pesticides in drinking water set by the U.S. Environmental Protection Agency (EPA). Residues of several pesticides were monitored in the ground water from Godavari river basin in Parbhani district for one year (2010-11). Most of the samples were found to be contaminated with residues of Hexachlorobenzene (HCB) and Dichloro-diphenyl-trichloroethane (DDT). Aldrin, endosulfan and heptachlor were also detected in some samples. Pesticides are indispensable in modern agriculture, but their use and/or misuse may lead to serious water quality problems– problems that could impair the use of water for crop and animal production or even human consumption. The impact of agricultural chemicals on groundwater quality has become an issue of national importance.